Availability and use of breeding habitat by the Red-legged Cormorant (Phalacrocorax gaimardi): Evidence for habitat selection - Millones, Ana (2010)
We studied the availability and use of breeding habitat by Red-legged Cormorants (Phalacrocorax gaimardi) to identify the factors involved in habitat selection. The species nests on cliff-faces. We identified cliffs suitable for nesting along 21km of coastline of the Ra Deseado, and recorded the characteristics of each, including the distance to the nearest potential foraging area. Previous research had indicated that zones of the river with a gravel substrate and 10m deep were preferred foraging areas for this species. Of the 16 cliffs identified as potential breeding sites, eight were used by Red-legged Cormorants for nesting. The probability of occurrence of active nests increased with the height and slope of cliffs and decreased with the distance to the nearest foraging area. Significant differences were observed between characteristics of cliffs that were used for breeding and those of available habitat in the environment. Cliffs higher than 12m, steeper than 85 and within 3km of a foraging area were the most frequently used but were not the most common in the environment. Factors that influence habitat selection by Red-legged Cormorants appear to be protection from predators and proximity to an abundant source of food. In this study, we also showed a non-random use of foraging sites. This species prefers zones with shallow water and gravel substrates.